Improving student’s speaking skill by using think-pair-share method with flashcard at grade VIIIB MTSN 6 Ngawi - Retnowati, Arumsyah Erlinda (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
Speaking has become an important skill in learning English as foreign language. The importance of speaking is shown by its function in the communication. By speaking English, we can communicate fluently with other people in the whole world. There are many factors which have influenced the students’ speaking skill. One of them is teaching method or strategy as external factor. Think-Pair-Share (TPS) or thinking in pairs is one type of cooperative learning method designed to influence the pattern of students’ interaction. This research has given evidence that TPS method is more effective than Direct Instruction method to teach speaking skill. This research is a classroom action research which consists of four steps to do: planning, action, observation and reflection. To collect the data of speaking skill, the researcher needs the instrument which is called a test. Besides speaking test instrument, researcher also used observation sheet to collect activities and development data. There is significant improvement on students speaking skill who taught by Think Pair Share method with flashcard media. It proved by the enhancement of average speaking score from 63.2 at the pretest result, become 73.2 at the first cycle and still increase to be 83 at the second cycle. The flashcard media were useful and effective to improve students’ speaking skill as described in finding and result of this study, as it improves class mastery achievement from 17.5% on the pretest, become 60% on the first cycle, and become 87.5% on the second cycle.